In Silico Study of Pomegranate Peel Polyphenols as Breast Anticancer - Ummah, Khoirotul; Zummah, Atiqoh (Stannum : Jurnal Sains dan Terapan Kimia, 2024)
Breast cancer is one of the causes of women’s death. Estrogen-α receptors are one of the targets for breast cancer treatment because it plays a role in cancer cell proliferation. Several studies have stated that Flavonoid compounds have high activity in inhibiting the growth of breast cancer cells. This study aims to inhibit polyphenolic compounds in pomegranate peel (gallic acid, cafeic acid, ellagic acid, and chlorogenic acid) against estrogen receptors-α through molecular docking. The 3D structures of the polyphenolic compounds were obtained from the PubChem database and the estrogen-α receptors from the Protein Data Base. Molecular docking simulations were carried out using AutoDock Vina and supporting software such as Biovia Discovery Studio Client 4.1, AutoDockTools 1.5.6, PyMOL, and LigPlot. The results showed that the four polyphenolic compounds had a better potential to inhibit estrogen-α receptors than tamoxifen. The inhibitory potential is evidenced by the low affinity of ligand-protein binding energy (approximately -5.4 to -9.0 kcal/mol). The phenol group of polyphenolic compounds can strengthen the ligand-protein interactions through hydrogen bonds with the active site of ER-ꭤ proteins. Hydrophobic and π-π stacking interactions between polyphenolic and the active site of proteins also support the inhibition potential of polyphenolic compounds. The conclusion is that the polyphenolic compounds in pomegranate peel have the potential as breast anticancers.